PENGARUH FAKTOR TEKNOLOGI, ORGANISASI, DAN LINGKUNGAN (TOE) TERHADAP ADOPSI E- COMMERCE DAN KINERJA BISNIS - Rahmawati, Alfi; Machmuddin, Nurlela (Fakultas Ekonomi Universitas Djuanda, 2025)
Digital transformation has become a critical driver of competitiveness among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Previous studies have confirmed the role of the Technology, Organization, Environment (TOE) framework in explaining technology adoption behavior. However, limited empirical research has explored how TOE factors simultaneously influence e-commerce adoption and how this adoption impacts MSME performance in Indonesia, particularly in regional cities such as Bogor. This study aims to examine the influence of technological, organizational, and environmental factors on e-commerce adoption and to analyze the role of e-commerce adoption in improving MSME performance in Bogor City. A quantitative approach was employed using a survey method. Data were collected from 211 MSME respondents in Bogor City who have utilized or are in the process of adopting e-commerce platforms. The research model was based on the TOE framework, and data analysis was conducted using Pearson correlation and path analysis with SPSS 25. The findings reveal that all three TOE factors significantly and positively influence e-commerce adoption. Among them, the environmental factor shows the strongest correlation (r = 0.689), followed by organizational (r = 0.639) and technological (r = 0.579) factors. Furthermore, e-commerce adoption has a significant positive correlation with MSME performance (r = 0.656). These results suggest that MSME organization, environmental support and technological capability are essential for enhancing e- commerce adoption and improving MSME performance.